The Ability of Gymnastics Motoric Perceptual Based on Local Culture for Early Childhood in Aceh Province - Muhammad Riski Kurniawan; Syamsulrizal Syamsulrizal; Razali Razali; Israwati Israwati (BIRCU, 2020)
Local culture-based gymnastics is a combination of Seudati dance with Saman dances movements as well as cheerful healthy exercises that are already in kindergarten. The purpose of this study was to determine the impact of the implementation of local culture-based exercise on the motorized perceptual ability of early childhood in Banda Aceh Kindergarten. This study uses a quantitative approach to the type of experimental research. Population and a sample of 30 students were selected by purposive sampling. Data collection techniques of motoric perceptual ability using tests: (1) Standing on the beam while touching the limbs as instructed by the teacher with eyes open, (2 ) Standing on the beam while touching the body as instructed by the teacher with eyes closed, (3) Jumping and landing in a line with two feet pressed together as instructed by the teacher with eyes open, (4) Jumping and landing in a line with two feet pressed together as instructed by the teacher with eyes closed , (5) Walking in balance, (6) Throwing a tennis ball into a basket with a distance of 2 meters. Before the data is analyzed, the research data is tested for the analysis requirements, namely the normality and homogeneity test. Then the data is analyzed using the t-test. Based on the results of data analysis obtained t count (18.455)> t table (2.045), thus it can be concluded that there is a significant influence between local culture-based exercise on the motoric perceptual ability of early childhood in Aceh kindergarten.